Development of double-layer anode material based on titanium nanotube for lithium batteries - Ablayeva, K.; Abduakhytova, D; Lepikhin, M (The 6th International Conference on Nanomaterials and Advanced Energy Storage Systems. Institute of Batteries LLP, Nazarbayev University, and PI “National Laboratory Astana”., 2018)
Recently, considerable efforts of specialists in the field of power sources are aimed at research on fully 3D microbatteries. The key advantage of a 3D microbattery is the higher surface area as compared to a planar film that allows for increased contact area with the electrolyte and more surface sites available for reversible reactions with lithium ions. This in turn leads to improved battery kinetics and increased power density while maintaining a small areal footprint. This peculiarity of the battery design can be provided by the use of 3D structured cathode/anode materials, the most attractive of which are highly ordered nanotubes (NTs) made of titanium dioxide with high capacity at fast charge and discharge rates and excellent long-term cycling characteristics. Apart from this crucial result, key to the successful fabrication of a full solid state microbattery is the conformal deposition of electrolyte on the self-supported electrode material to preserve the 3D architecture.
Keywords: 3D microbatteries; lithium batteries